2019
DOI: 10.1177/1352458519829698
|View full text |Cite
|
Sign up to set email alerts
|

Childhood multiple sclerosis is associated with reduced brain volumes at first clinical presentation and brain growth failure

Abstract: Background: Paediatric multiple sclerosis (pedMS) patients at a single site were shown to have reduced brain volumes and failure of age-expected brain growth compared to healthy controls. However, the precise time of onset of brain volume loss remains unclear. Objective: To longitudinally study brain volumes in a multi-centre European cohort at first presentation and after 2 years. Methods: Brain volumes of high-resolution magnetic resonance imaging (MRI) data from 37 pedMS patients at first presentation prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…This suggests that the biological onset of NMDARE in children might precede the clinical presentation, resulting in brain volume loss already present on the initial MRI. Similar observations, that is, reduced brain volumes already at disease onset, have also been reported in children with multiple sclerosis 18,32 …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This suggests that the biological onset of NMDARE in children might precede the clinical presentation, resulting in brain volume loss already present on the initial MRI. Similar observations, that is, reduced brain volumes already at disease onset, have also been reported in children with multiple sclerosis 18,32 …”
Section: Discussionsupporting
confidence: 73%
“…Similar observations, that is, reduced brain volumes already at disease onset, have also been reported in children with multiple sclerosis. 18,32 Limitations of the study include the retrospective study design, the relatively small sample size, especially in some of the subgroup analyses, and the lack of neuropsychological data. As this study aimed at exploring new clinical predictors, multiple comparison was not applied.…”
Section: Clinical and Mri Predictors Of Disease Outcome And Severitymentioning
confidence: 99%
“…One study of Canadian children and one from France reported that children with MS have reduced whole brain volumes when assessed at a single time point and lower-than-expected brain growth over multiple time points compared with matched controls. 45,46 In the Canadian study, reduced regional brain growth in the thalamus was especially marked. Inconsistent associations have been reported between gray matter involvement and white matter lesion volume.…”
Section: Structural and Functional Mri Analysesmentioning
confidence: 93%
“…11 PoMS is associated with failure of age-expected brain growth during childhood and early adolescence, and brain atrophy from disease-onset to mid-adolescence and into adulthood. [12][13][14] Findings suggest that T2 and T1 lesion volumes are comparable in patients with paediatric-onset and adult-onset MS when matched for disease duration. 15 Higher T2 lesion volumes correlate with reduced thalamic volumes in paediatric patients, and total thalamic volumes are reduced relative to age-expected values, even after correcting for reductions in head size.…”
Section: Introductionmentioning
confidence: 99%